Automobility and Resilience: A Global Perspective - Kenworthy, Jeffrey; Newman, Peter (Routledge, 2014)
Automobility. and. resilience. A. global. perspective. Peter. Newman. and. Jeffrey. Kenworthy. Automobility is highly related to automobile dependence, the idea we coined in 1989 to describe the way we have created cities and regions ...